Isolated Fetal Cardiac Abnormalities: Are They Really Isolated? - Razavi, Armin S.; Chasen, Stephen T. (American Journal of Perinatology Reports, 2018)
Objective To determine the rate of unsuspected noncardiac abnormalities in newborns suspected to have isolated cardiac abnormalities in the second trimester.Study Design A review of the ultrasound database from the Weill Cornell Medical Center identified fetuses with a suspected cardiac abnormality from January 2006 to November 2016. Cases with prenatally suspected noncardiac structural abnormalities, abnormal fetal or neonatal karyotype or microarray, and those who delivered at an outside institution or underwent abortion were excluded. Neonatal records were reviewed to confirm prenatal findings and to identify anomalies not suspected in the second trimester.Results Sixty-eight live births met the inclusion criteria. Five newborns (7.4%) had major abnormalities not identified in the second trimester. Three newborns had an imperforate anus. One newborn had left hydronephrosis and absent right lung, and one had hemifacial microsomia and fused ribs. All five newborns with unsuspected anomalies were in the group with suspected conotruncal anomalies, with a 11.9% rate of unsuspected anomalies versus 0% in those with nonconotruncal cardiac anomalies (p = 0.15).Conclusion Patients with a suspected isolated fetal cardiac anomaly on ultrasound should be aware of the possibility of other major structural abnormalities, especially in cases of conotruncal cardiac anomalies.
Keywords: cardiac abnormality; cardiac anomaly; conotruncal; noncardiac abnormalities; noncardiac anomalies